Thermal conductivity measurements and modeling of ceramic fiber insulation materials. (February 2019) - Headley, Alexander J.; Hileman, Michael B.; Robbins, Aron S.; Piekos, Edward S.; Stirrup, Emily K.; Roberts, Christine C.
Highlights: Thermal conductivity data collected changing temperature and compression. Effective medium model developed to capture variation in conductivity. Model tuned to data collected in an air environment. Model found to be in good agreement with collected and published data sets. Model could aid in thermal designs in operational environments. Abstract: Ceramic fiber insulation materials are used in numerous applications (e.g. aerospace, fire protection, and military) for their stability and performance in extreme environments. However, the thermal properties of these materials have not been thoroughly characterized for many of the conditions that they will be exposed to, such as high temperatures, pressures, and alternate gaseous atmospheres. The resulting uncertainty in the material properties can complicate the design of systems using these materials. In this study, the thermal conductivity of two ceramic fiber insulations, Fiberfrax T-30LR laminate and 970-H paper, was measured as a function of atmospheric temperature and compression in an air environment using the transient plane source technique. Furthermore, a model is introduced to account for changes in thermal conductivity with temperature, compression, and ambient gas. The model was tuned to the collected experimental data and results are compared. The tuned model is also compared to published data sets taken in argon, helium, and hydrogen environments and agreement is discussed.